2017
DOI: 10.1186/s12936-017-2057-8
|View full text |Cite
|
Sign up to set email alerts
|

Imported malaria in Spain (2009–2016): results from the +REDIVI Collaborative Network

Abstract: BackgroundImported malaria is a frequent diagnosis in travellers and migrants. The objective of this study was to describe the epidemiological and clinical characteristics of patients diagnosed with imported malaria within a Spanish collaborative network registering imported diseases (+REDIVI). In addition, the possible association between malaria and type of case, gender, age or area of exposure was explored.MethodsCases of imported malaria were identified among all cases registered in the +REDIVI database du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 20 publications
5
27
1
Order By: Relevance
“… 29 , 30 , 31 Other studies, however, reported an increase of imported malaria incidence, gradually in Spain or the United States and more sharply in recent years in the Netherlands and Germany. 22 , 32 , 33 , 34 The rising number of cases was attributed to the increase in the number of travelers toward endemic areas or to population migrations for economic or political reasons (refugees). The balance between these different mechanisms may explain the complexity of the temporal patterns observed in several countries with imported malaria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 29 , 30 , 31 Other studies, however, reported an increase of imported malaria incidence, gradually in Spain or the United States and more sharply in recent years in the Netherlands and Germany. 22 , 32 , 33 , 34 The rising number of cases was attributed to the increase in the number of travelers toward endemic areas or to population migrations for economic or political reasons (refugees). The balance between these different mechanisms may explain the complexity of the temporal patterns observed in several countries with imported malaria.…”
Section: Discussionmentioning
confidence: 99%
“…This elevation could be related to the increase in age of traveers, as observed in the United Kingdom and United States. 34,40,42 The reduction of malaria immunity in Africans living in France may have played a role; however, there is a lack of data about this variable. 43 Considering the higher incidence of severe cases, the concomitant stability in the number and proportion of deaths is surprising.…”
Section: Discussionmentioning
confidence: 99%
“…used an effective prophylaxis [ 27 ]. Moreover, in a recent Spanish study considering only the subgroup of travellers with P. ovale / P. vivax malaria, these patients had also taken chemoprophylaxis significantly more frequently than those with non- P. ovale / P. vivax malaria (35.5% vs. 2.7%) [ 28 ]. These results reinforce the idea that current prophylaxis does not adequately act on P. ovale spp.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have identified Plasmodium falciparum as the predominant species responsible for imported malaria, not only in Spain [20,54,55], but also in other countries such as the United States [56], the United Kingdom [57] and France [58]. It must be taken into account that not many of these travellers and immigrants carry out correct anti-malarial prophylaxis [59], so informing people of the need to take appropriate preventive measures before travelling to endemic countries is essential.…”
Section: Imported Malariamentioning
confidence: 99%
“…Other countries, such as France, Italy and the United Kingdom, have also seen a greater number of imported malaria cases from former colonies with which they have historical and economic ties [55,56]. Among international travellers, some cases are also associated with travel to Latin America and Asia [57].…”
Section: Imported Malariamentioning
confidence: 99%